Pendekatan Akulturasi Islam Nusantara dalam Pembelajaran PAI untuk Pembentukan Kesadaran Ekologis Peserta Didik - Renita Renita; Dika Tripitasari; Ahdar Ahdar (Reflection : Islamic Education Journal, 2026)
The global ecological crisis is not only a scientific issue but also reflects the decline of human moral and spiritual awareness toward nature. This study aims to examine the acculturation approach of Islam Nusantara in Islamic Religious Education (PAI) learning as an effort to foster students’ ecological awareness. The research employed a qualitative library research method using various relevant sources, including books, national and international journal articles, and educational policy documents. Data analysis was conducted through data reduction, thematic presentation, and interpretive-analytical conclusion drawing. The findings indicate that Islam Nusantara, as a product of the acculturation between universal Islamic values and local Nusantara wisdom, contains various ecological traditions such as sasi, subak, and hutan larangan (forbidden forests), which can be contextually integrated into PAI learning. The developed learning model includes the use of local wisdom as learning resources, participatory project-based learning methods, and thematic Qur’anic interpretation related to environmental issues. The ecotheological approach of Islam Nusantara is considered effective in connecting religious teachings with students’ ecological realities, thereby fostering a religious-ecological character that views environmental preservation as part of worship. Although challenges remain in theological, pedagogical, and institutional aspects, this approach contributes strategically to shaping environmentally responsible Muslim generations.